Efficiency of pH-Sensitive Fusogenic Polymer-Modified Liposomes as a Vaccine Carrier. (4th February 2013) - Watarai, Shinobu; Iwase, Tana; Tajima, Tomoko; Yuba, Eiji; Kono, Kenji
Abstract : The usefulness of pH-sensitive fusogenic polymer-(succinylated poly(glycidol)-(SucPG-) modified liposomes as a vaccine carrier in the induction of immune responses was evaluated. Mice were intraperitoneally immunized with ovalbumin- (OVA-) containing SucPG-modified liposomes. After immunization, significant OVA-specific antibodies were detected in the serum. When sera were analyzed for isotype distribution, OVA-specific IgG1 antibody responses were noted in mice immunized with OVA-containing polymer-unmodified liposomes, whereas immunization with OVA-containing SucPG-modified liposomes resulted in the induction of OVA-specific IgG1, IgG2a, and IgG3 Ab responses. In spleen lymphocytes from mice immunized with OVA-containing SucPG-modified liposomes, both IFN- γ -(Th1-type-) and IL-4-(Th2 type-) specific mRNA were detected. Moreover, substantial production of IFN- γ and IL-4 was demonstrated in spleen cells from OVA-containing SucPG-modified liposomes in vitro . These results suggest that the pH-sensitive fusogenic polymer-(SucPG-) modified liposomes would serve effectively as an antigen delivery vehicle for inducing Th1 and Th2 immune responses.